Analysis of full-scale aircraft impact to reinforced concrete and steel plate reinforced concrete multiple barriers protecting nuclear power plants. (October 2020) - Sadiq, Muhammad; Khaliq, Wasim; Ilyas, Muhammad; Khushnood, Rao Arsalan; Khan, Shaukat Ali; Rong, Pan
Abstract: This paper investigates the effectiveness of multiple barriers employed in safety-related concrete structures of nuclear power plants against aircraft impact. These barriers are constructed using reinforced concrete (RC) and steel plate reinforced concrete (SC) structural panels. The performance of such multiple barriers against the impact of a missile or an aircraft is found in many published studies. However, the influence of aircraft impact on the second barriers needs further study. To evaluate the impact resistance of multiple barriers, analysis of full-scale aircraft against RC and SC as the first panel with two different thicknesses (60 cm and 75 cm) are investigated by using finite element code LS-DYNA. The fracture process of aircraft and target panels, damage to the first panel, residual velocities, plastic strain of rebars, impact loads to second panel and energy balance histories are evaluated. The comparison of LS-DYNA analysis results indicates that the maximum force on the second rigid panels is reduced to a maximum of 61% owing to the SC panels. The SC panels experienced fewer residual velocities and impact loads thus showing better performance as compared to the conventional RC panels having the same thicknesses. Resultantly, it is possible to reduce the thickness and cost of safety-related RC structures by adopting steel plates in the design. The finite element-based methodology adopted in this study may be employed to predict the precise response of safety-related structures (barriers) against military and commercial aircraft impacts.